Factors Affecting Chronic Energy Deficiency among Pregnant Women in East Nusa Tenggara Province, Indonesia - Rachmi, Rizkia; Marjan, Avliya Quratul; Sufyan, Dian Luthfiana; Wahyuningsih, Utami (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aims to investigate the relationship between maternal and household characteristics with the Chronic Energy Deficiency (CED) occurrence among pregnant women in East Nusa Tenggara (ENT). CED was observed through Mid-Upper Arm Circumference (MUAC) measurement of <23.5 cm. Utilizing a cross-sectional design using secondary data from the 2018 Indonesia Basic Health Survey (Riskesdas) involving 387 pregnant women. Bivariate analysis (chi-square test) and multivariate analysis (multiple logistic regression) were conducted. Significant associations with the CED included parity (p=0.002), education level (p=0.018), access to hospital (transportation mode) (p=0.032), and access to primary healthcare facilities (travel time) (p=0.032). Multivariate analysis identified parity as the most influential variable for the CED occurrence among pregnant women (p=0.016; OR=1.868). In conclusion, mothers with a parity of less than two or more than three children had a higher risk of experiencing CED during pregnancy in ENT. To prevent CED and its consequences, it is recommended to emphasize family planning, address parity concerns, and prioritize maternal nutritional status before and during pregnancy.